Evaluasi Program Bantuan Peningkatan Karir Pendidik Sekolah Menengah Pertama (Studi Evaluasl Model CIPP pada Musyawarah Guru Mata Pelajaran sekolah Menengah Pertama di Dinar Pendidikan Kabupaten Bogor) - Surdarno (Institut Agama Islam Sahid (INAIS) Bogor, 2019)
The educator career enhancement program is an education and training activity for educators to improve the professionalism of their performance and have an impact on obtaining rewards for introducing career paths (class and functional position of educator). Various obstacles have been found as obstacles to optimizing this program so that it is necessary to evaluate the program in order to achieve effectiveness in supporting program objectives. This study aims to identify and evaluate the Career Improvement Assistance Program for Junior High School Educators (SMP) through the Subject Teacher Consultation (MGMP) which has been running since 2013 as a basis for recommendations in decision making and planning follow-up programs. This type of program evaluation research uses a descriptive qualitative approach to the CIPP evaluation model (Context, Input, Process, Product) developed by Daniel Leroy Stufflebeam. Data collection instruments were obtained through interview techniques, documentation studies, observations and questionnaires. Data analysis was carried out through data collection, data reduction, conclusion on drawing, data display, data verification and conclusions. The results showed that the evaluation of the program's Context was in the